1952
DOI: 10.1002/hlca.19520350442
|View full text |Cite
|
Sign up to set email alerts
|

Versuche zur quantitativen Erfassung der bei der Resorption von Neutralfett eintretenden Spaltung

Abstract: An investigation was carried out on the absorption of neutral fats, with the purpose of studying the hydrolysis taking place during this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1953
1953
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The origin of the fecal fat and the relative concentrations from dietary and endogenous sources were not studied here, although it has been suggested that endogenous fat excretion may be increased in animals with biliary diversion (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the fecal fat and the relative concentrations from dietary and endogenous sources were not studied here, although it has been suggested that endogenous fat excretion may be increased in animals with biliary diversion (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…This step is irreversible in that glycerol from ingested triglyceride is not reacylated in the lumen (49,50). Incubation of triglyceride with high concentrations of pancreatic lipase in vitro results in complete digestion of triglyceride to fatty acid and glycerol (51,52).…”
Section: Fat Digestion In Manmentioning
confidence: 99%
“…Reiser, Bryson, Carr & Kuiken (1952) claimed that 25-45% of triglyceride is completely hydrolysed to glycerol, the remaining 55-75 % being hydrolysed to monoglyceride: this is equivalent to 75-80 % of the fatty acid being liberated. Bernhard, Wagner & Ritzel (1952) also found that 24-53 % of the glycerol of triglyceride eaten must have been liberated during digestion. Borgstr6m (1954 a) has shown that di-and triglycerides can be synthesized from monoglyceride during digestion, a finding which throws some doubt on the validity of deductions from this type of experiment.…”
Section: University Ofmentioning
confidence: 93%